A trajetória do movimento e da participação: a origem da organização sindical na educação - Lima, Claudete Veiga de (1999)
Historical rescue of the organized movement of the technical and administrative worker of the UFRJ The present study has as a central objective, the di scription of the way the ascent of the organized movement of the technical and administrative workers of the UFRJ - inicial1y understood as in the association figure - unleashed of the transfomations of this representatitive entity to 'Category Sindicate'. To be the research subjects-, sindicate leaders were selected , whom had a significant insertion in this process The main protagonists relate remarkable facts, which many of them are not found in registers of the studied of organization heaps. The document analysis. which, identify this history, was also added to this study. The emphasis of this work is turned to descriptive research The field research take place in the Education Workers of the UFRJ. The analysis of the empirical material indicates that the transfomations process - from the association figure to sindicate figure - dos not happen in the fonnal way, which happened in 1993. But from the 80's on, when a group of workers takes part in the organizations and start to demand political and c1aining practice, estabilishing a difference from the attending and recreative procedures, which permeate the previous administrations. Regarding the description of this history, however, the intension was not only to point a linear evolution, but also identify the retrogressions which determined some moments of insteadiness., as well to take a second evaluation of the involved subjects. It constitutes so an evaluation instrument of the practices, objectives, politics and cultures which pervade the operation of this movement creating questions which can contribute to surmont possible mistakes or restraints in the present moment.